PENGARUH SET KESEMPATAN INVESTASI, PROFITABILITAS, KEPEMILIKAN PEMERINTAH, DAN FASILITAS PERPAJAKAN TERHADAP TARIF PAJAK EFEKTIF PERUSAHAAN YANG TERDAFTAR PADA KOMPAS 100 - Etika Muhsinah Lubis; Yusralaini -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the effect of investment opportunity set, profitability, government ownership and tax incentive to the corporate effective tax rate listed at Kompas 100. This study used a secondary data. the sample of this study comprised of 43 companies with two years observed which were selected through purposive sampling. Data analysis for hypothesis test was done with multiple regression analysis. The result of this study give evidence that investment opportunity set and profitability have influence to the corporate effective rate at significance level 5%. While government ownership and tax incentive have not influence to the corporate effective rate at significance level 5%. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 39,1%, while the remaining 60,9% is influenced by other variables that not examined in this study.Keywords: investment opportunity set, profitability, government ownership, tax incentive and the corporate effective tax rate.